Zinc-iron composite oxide coated titanium dioxide hollow fiber and its preparation method and application
Through the preparation of zinc-iron-iron composite oxide-coated titanium dioxide hollow fibers, the problems of impedance mismatch and single loss of traditional absorbing materials are solved, and strong absorption performance and impedance matching are achieved under small thickness. It is suitable for electromagnetic wave absorbing devices .
Patent Information
- Application Number
- CN202210151514.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-18
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-02-18
AI Technical Summary
Traditional magnetic metal powder absorbing materials are prone to oxidation, have high density and high conductivity, resulting in impedance mismatch, making it difficult to achieve strong loss and impedance matching at the same time. The loss mechanism of a single component metal oxide absorbing material is single, making it difficult to meet the needs of electromagnetic wave absorption.
Zinc-iron composite oxide is used to coat titanium dioxide hollow fibers, and prepared by electrospinning, calcining and hydrogen reduction to form a composite hollow fiber structure of zinc oxide, iron tetraoxide and titanium dioxide, and optimize impedance matching and loss capacity.
Achieve strong absorption performance and good impedance matching under small thickness. The synergistic effects of zinc oxide, iron tetroxide and titanium dioxide enhance the loss and scattering of electromagnetic waves. The material's reflection loss on electromagnetic waves at high frequencies reaches -57.84 dB.
Smart Images

Figure CN114665279B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic wave absorbing materials, and specifically relates to a zinc-iron composite oxide-coated titanium dioxide hollow fiber and a preparation method and application thereof. The composite material can be used as an electromagnetic wave absorbing material. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Traditional magnetic metal powder absorbers have high saturation magnetization and magnetic permeability, and high magnetic loss capacity, but they are easily oxidized and have high density, which is not conducive to the portability of equipment; in addition, the high electrical conductivity of magnetic metal powders can easily cause reflection of electromagnetic waves, resulting in impedance mismatch, which will significantly reduce the material's absorbing performance. In addition, at present, single-component metal oxide absorbers have a single loss mechanism, making it difficult to achieve strong loss and impedance matching at the same time. Summary of the invention
[0004] In order to make the absorbing material have both strong loss and good impedance matching, a zinc-iron composite oxide coated titanium dioxide hollow fiber and a preparation method and application thereof are provided. When the material is used for electromagnetic wave absorption, it has good impedance matching and strong loss capacity, and has strong absorbing performance when the thickness is small.
[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a zinc-iron composite oxide-coated titanium dioxide hollow fiber, comprising the following steps:
[0007] The zinc salt and the iron salt are uniformly dispersed in a solvent by using a surfactant, and then electrospinning is performed to obtain zinc-iron based fibers;
[0008] The zinc-iron-based fiber is heated and calcined in air, and then reduced in hydrogen to obtain a precursor;
[0009] The precursor is mixed with a titanium source and ethanol to undergo a solvothermal reaction to obtain a product;
[0010] Among them, zinc exists in the form of zinc oxide, and iron exists in the form of ferroferric oxide.
[0011] In a second aspect, the present invention provides a zinc-iron composite oxide coated titanium dioxide hollow fiber prepared by the preparation method, wherein zinc exists in the form of zinc oxide, iron exists in the form of ferroferric oxide, the zinc oxide and ferroferric oxide composite exists in the form of hollow fibers, and titanium dioxide is coated on the surface of the hollow fibers.
[0012] In the third aspect, the application of the zinc-iron composite oxide-coated titanium dioxide hollow fiber in the direction of electromagnetic wave absorption;
[0013] Especially in the application of preparing electromagnetic wave absorption devices.
[0014] In a fourth aspect, an electromagnetic wave absorbing device is prepared by coating titanium dioxide hollow fibers with the zinc-iron composite oxide.
[0015] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0016] 1) The composite hollow fiber of zinc oxide and ferroferric oxide coated with titanium dioxide prepared by the preparation method, on the one hand, zinc oxide is a low-loss wave-transmitting material, which can optimize the impedance matching of the material and allow electromagnetic waves to smoothly enter the interior of the material without reflection; on the other hand, since titanium dioxide is a narrow bandgap semiconductor with semi-metallic properties, the presence of titanium dioxide improves the conductivity of the material, enhances the conductivity loss, and has a strong loss to the incident electromagnetic wave; thirdly, ferroferric oxide has a certain magnetic loss capacity, which is beneficial to the loss of the incident electromagnetic wave; fourthly, the presence of the hollow structure can not only optimize the impedance matching of the material, but also cause multiple scattering of the electromagnetic wave, thereby enhancing the loss of the material to the electromagnetic wave; finally, the synergistic effect of zinc oxide and ferroferric oxide further optimizes the impedance matching, and the synergistic effect of the ternary components of zinc oxide, ferroferric oxide and titanium dioxide increases multiple losses and scattering.
[0017] 2) Compared with the prior art, the synthesis method of the zinc oxide and ferroferric oxide composite coated titanium dioxide composite hollow fiber of the present invention is simple, and only requires one electrospinning, one calcination, one hydrogen reduction and one solvent thermal reaction to obtain the final product. The prepared zinc oxide and ferroferric oxide composite coated titanium dioxide hollow fiber material has a uniform diameter, and no other by-products are generated during the solvent reaction thermal process.
[0018] 3) The composite hollow fiber of zinc oxide and ferroferric oxide coated titanium dioxide is compounded with paraffin to obtain an absorbing material, and the reflection loss of electromagnetic waves at high frequency (15.68GHz) reaches -57.84dB, and the matching thickness is 4.96mm. The composite hollow fiber material of zinc oxide and ferroferric oxide coated titanium dioxide has high absorbing performance and has wide application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0020] Figure 1This is the XRD diagram of the composite hollow fiber of zinc oxide and ferroferric oxide coated with titanium dioxide prepared in Example 1.
[0021] Figure 2 In the figure, Figure a is a SEM image of the precursor prepared in step (3) of Example 1, and Figure b is a SEM image of the zinc oxide and ferrosoferric oxide composite coated titanium dioxide composite hollow fiber finally obtained in Example 1.
[0022] Figure 3 TEM image of the composite hollow fiber of zinc oxide and ferroferric oxide coated with titanium dioxide obtained in Example 1.
[0023] Figure 4 Figure a is the real part of the dielectric constant of the zinc oxide and ferroferric oxide composite-coated titanium dioxide composite hollow fiber prepared in Example 1, Figure b is the imaginary part of the dielectric constant, and Figure c is the dielectric loss tangent.
[0024] Figure 5 This is the impedance matching diagram of the zinc oxide and ferroferric oxide composite-coated titanium dioxide composite hollow fiber prepared in Example 1.
[0025] Figure 6 This is the reflection loss diagram of the composite hollow fiber absorber of zinc oxide and ferroferric oxide coated with titanium dioxide prepared in Example 1.
[0026] Figure 7 This is the SEM image of the sample prepared in Comparative Example 1.
[0027] Figure 8 This is the reflection loss diagram of the solid prepared in Comparative Example 1. DETAILED DESCRIPTION
[0028] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0029] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0030] In a first aspect, the present invention provides a method for preparing a zinc-iron composite oxide-coated titanium dioxide hollow fiber, comprising the following steps:
[0031] The zinc salt and the iron salt are uniformly dispersed in a solvent by using a surfactant, and then electrospinning is performed to obtain zinc-iron based fibers;
[0032] The zinc-iron-based fiber is heated and calcined in air, and then reduced in hydrogen to obtain a precursor;
[0033] The precursor is mixed with a titanium source and ethanol to undergo a solvothermal reaction to obtain a product;
[0034] Among them, zinc exists in the form of zinc oxide, and iron exists in the form of ferroferric oxide.
[0035] The fiber structure is formed by self-assembly of iron ions, zinc ions and surfactants through coordination bonds, and then the zinc-iron hollow fiber precursor is formed after calcination in air to remove the surfactant, and magnetic ferroferric oxide is obtained under a reducing atmosphere. Finally, a solvent thermal reaction is carried out with a titanium source, and the titanium source is converted into titanium dioxide and attached to the surface of the zinc oxide-ferroferric oxide composite hollow fiber precursor. The two react to form a zinc oxide and ferroferric oxide composite-coated titanium dioxide composite hollow fiber material.
[0036] The zinc-iron based fiber is heated and calcined in air to obtain a zinc oxide and zinc ferrite composite hollow fiber. The zinc oxide and zinc ferrite composite hollow fiber is reduced in hydrogen to obtain a zinc oxide and ferroferric oxide composite hollow fiber precursor.
[0037] The prepared composite hollow fiber contains Zn, Fe, Ti and O elements. Among them, Zn and O elements exist in the form of ZnO, Fe and O elements exist in the form of Fe3O4, and Ti and O elements exist in the form of TiO2. The three are evenly mixed to finally form a hollow fiber material of zinc oxide and ferroferric oxide composite coated with titanium dioxide.
[0038] In some embodiments, the zinc salt is zinc nitrate hexahydrate, zinc chloride, or zinc acetate dihydrate.
[0039] In some embodiments, the iron salt is ferric acetylacetonate, ferric nitrate nonahydrate, ferric chloride, or ferric acetate tetrahydrate.
[0040] Preferably, the surfactant is polyvinyl pyrrolidone or polyacrylonitrile. These two surfactants are used for bonding and stabilizing the morphology and contain only carbon, hydrogen and oxygen elements. The surfactant in the fiber can be removed after calcination in air, thereby obtaining a hollow fiber structure.
[0041] In some embodiments, the titanium source is tetrabutyl titanate, tetraethyl titanate, or tetraisopropyl titanate.
[0042] Preferably, the solvent is N,N-dimethylformamide.
[0043] Preferably, the mass of zinc salt, iron salt and surfactant added to each milliliter of solvent is 0.01-0.4g, 0.01-0.4g, 0.01-0.8g.
[0044] Further preferably, the mass of zinc salt, iron salt and surfactant added to each milliliter of solvent is 0.01-0.2g, 0.01-0.2g, 0.1-0.3g.
[0045] In some embodiments, the electrospinning voltage is 8-15 kV and the feed rate is 0.1-0.8 mL / h;
[0046] Preferably, the voltage of electrospinning is 10-13 kV, and the feed rate is 0.1-0.5 mL / h;
[0047] Further preferably, the voltage of electrospinning is 11 kV and the feed rate is 0.3 mL / h.
[0048] During the electrospinning process, by controlling the voltage of electrospinning, the zinc salt and the iron salt diffuse to the outside of the fiber, and the polyvinyl pyrrolidone is calcined when heated and calcined in air, which helps to form a hollow structure. The above addition ratio, voltage and feed rate are conducive to the formation of zinc-iron hollow fiber precursors.
[0049] In some embodiments, the zinc-iron-based fiber is heated and calcined in air at a temperature of 300-600° C., a heating rate of 1-5° C. / min, and a reaction time of 0.5-5 h.
[0050] Preferably, the heating calcination temperature is 400-550°C, the heating rate is 1-3°C / min, and the reaction time is 1-3h.
[0051] During the heating and calcining process, the zinc-iron-based fiber is oxidized into zinc oxide composite zinc ferrite hollow fiber. If the heating and calcining temperature is too low, the surfactant in the fiber cannot be removed, the hollow structure cannot be obtained, and by-products are easily generated. If the calcining temperature is too high, the fiber cannot withstand it and the structure is destroyed.
[0052] Preferably, the method of reducing the precursor in hydrogen is: calcining at 450-550° C. for 1.5-2.5 h in a hydrogen atmosphere to obtain the precursor; more preferably, the calcination temperature is 500° C. and the calcination time is 2 h.
[0053] The sample is placed in a tube furnace, high-purity hydrogen is introduced, the reduction temperature and time of trivalent iron are set, and it is cooled naturally to room temperature. After reduction at the set temperature and time, the sample is black in color and has good magnetic properties, which can be preliminarily judged to be triferric iron tetroxide. This is then confirmed by XRD.
[0054] In some embodiments, the mass ratio of the precursor to the titanium source is 0.05-1:0.05-1; preferably 0.05-0.5:0.05-0.5.
[0055] Preferably, the temperature of the solvothermal reaction of the precursor and the titanium source is 100-200° C., and the reaction time is 6-15 h;
[0056] More preferably, the reaction temperature is 120-180° C., and the reaction time is 8-13 h.
[0057] In this process, the titanium source is converted into titanium dioxide and attached to the surface of the zinc oxide-iron tetroxide composite hollow fiber precursor, and the two react to form a zinc oxide and iron tetroxide composite-coated titanium dioxide composite hollow fiber material.
[0058] In a second aspect, the present invention provides a zinc-iron composite oxide coated titanium dioxide hollow fiber prepared by the preparation method, wherein zinc exists in the form of zinc oxide, iron exists in the form of ferroferric oxide, the zinc oxide and ferroferric oxide composite exists in the form of hollow fibers, and titanium dioxide is coated on the surface of the hollow fibers.
[0059] In the third aspect, the application of the zinc-iron composite oxide-coated titanium dioxide hollow fiber in the direction of electromagnetic wave absorption;
[0060] Especially in the application of preparing electromagnetic wave absorption devices.
[0061] In a fourth aspect, an electromagnetic wave absorbing device is prepared by coating titanium dioxide hollow fibers with the zinc-iron composite oxide.
[0062] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0063] Example 1
[0064] (1) 1 g of polyvinyl pyrrolidone, 0.439 g of zinc acetate dihydrate, and 0.706 g of ferric acetylacetonate were dissolved in 6 mL of N,N-dimethylformamide solution, stirred for 60 min, and then transferred into a 15 mL syringe. The positive voltage at the needle tip was set to 11 kV, the receiving distance was set to 25 cm, and the spinning solution feed rate was set to 0.2 mL / h for spinning. After spinning, the obtained zinc-iron-based fiber was dried at 50 ° C for 6 h, and torn off with tweezers for later use;
[0065] (2) The fiber obtained in (1) was placed in a crucible and placed in a tube furnace. The temperature was raised to 500°C at 2°C / min in an air atmosphere and calcined for 2 h, followed by natural cooling to room temperature.
[0066] (3) The fiber obtained in step (2) was placed in a crucible and placed in a tubular furnace. The temperature was raised to 450°C at 2°C / min in a hydrogen atmosphere and calcined for 2 h, followed by natural cooling to room temperature.
[0067] (4) 0.1 g of the fiber obtained in (3) was mixed with 0.1 mL of tetrabutyl titanate and ethanol, and the mixture was subjected to solvothermal reaction at 150° C. for 12 h, and then naturally cooled to room temperature.
[0068] Figure 1 This is the XRD diagram of the composite hollow fiber of zinc oxide and ferroferric oxide coated with titanium dioxide prepared in Example 1, confirming that zinc oxide, ferroferric oxide and titanium dioxide are prepared.
[0069] Figure 2 Figure a is a SEM image of the precursor prepared in step (3) of Example 1, with a diameter of about 220 nm and a uniform particle size distribution; Figure b is a SEM image of the zinc oxide and ferrous oxide composite coated titanium dioxide composite hollow fiber finally obtained in Example 1, with a diameter of about 235 nm, and the fiber morphology is well maintained without damage.
[0070] Figure 3 The TEM image of the solid obtained in Example 1 shows that the solid has a hollow structure and a shell thickness of about 7 nm. Figure 3 It can be confirmed that the solid obtained in Example 1 has a hollow core-shell structure.
[0071] Example 2
[0072] (1) 1 g of polyvinyl pyrrolidone, 0.439 g of zinc acetate dihydrate, and 0.706 g of ferric acetylacetonate were dissolved in 6 mL of N,N-dimethylformamide solution, stirred for 60 min, and then transferred into a 15 mL syringe. The positive voltage at the needle tip was set to 11 kV, the receiving distance was set to 25 cm, and the spinning solution feed rate was set to 0.2 mL / h for spinning. After spinning, the obtained zinc-iron-based fiber was dried at 50 ° C for 6 h, and torn off with tweezers for later use;
[0073] (2) The fiber obtained in (1) was placed in a crucible and placed in a tube furnace. The temperature was raised to 500°C at 2°C / min in an air atmosphere and calcined for 3 h, followed by natural cooling to room temperature.
[0074] (3) Take the fiber obtained in (2), put it into a crucible, and place it in a tube furnace. In a hydrogen atmosphere, increase the temperature to 500°C at 2°C / min and calcine for 2h, and then cool it naturally to room temperature.
[0075] (4) 0.1 g of the fiber obtained in (3) was mixed with 0.1 mL of tetrabutyl titanate and ethanol, and the mixture was subjected to solvothermal reaction at 150° C. for 12 h, and then naturally cooled to room temperature.
[0076] Example 3
[0077] (1) 1 g of polyvinyl pyrrolidone, 0.439 g of zinc acetate dihydrate, and 0.706 g of ferric acetylacetonate were dissolved in 6 mL of N,N-dimethylformamide solution, stirred for 60 min, and then transferred into a 15 mL syringe. The positive voltage at the needle tip was set to 11 kV, the receiving distance was set to 25 cm, and the spinning solution feed rate was set to 0.2 mL / h for spinning. After spinning, the obtained zinc-iron-based fiber was dried at 50 ° C for 6 h, and torn off with tweezers for later use;
[0078] (2) The fiber obtained in (1) was placed in a crucible and placed in a tube furnace. The temperature was raised to 500°C at 2°C / min in an air atmosphere and calcined for 2 h, followed by natural cooling to room temperature.
[0079] (3) Take the fiber obtained in (2), put it into a crucible, and place it in a tube furnace. In a hydrogen atmosphere, increase the temperature to 500°C at 2°C / min and calcine for 2h, and then cool it naturally to room temperature.
[0080] (4) 0.1 g of the fiber obtained in (3) was mixed with 0.1 mL of tetrabutyl titanate and ethanol, and the mixture was subjected to solvothermal reaction at 150° C. for 12 h, and then naturally cooled to room temperature.
[0081] Performance Testing
[0082] The zinc oxide and ferroferric oxide composite coated titanium dioxide composite hollow fiber and paraffin in Example 1 were mixed to obtain a zinc oxide and ferroferric oxide composite coated titanium dioxide composite hollow fiber composite absorbing material. The electromagnetic parameters were tested using an Agilent Technologies E8363A electromagnetic wave vector network analyzer, and the absorbing performance of the material was calculated based on the electromagnetic parameters to obtain the following: Figure 4 , Figure 5 Results shown.
[0083] Figure 4 It can be seen that the zinc oxide and ferroferric oxide composite coated titanium dioxide composite hollow fiber composite absorbing material has strong dielectric loss.
[0084] Figure 5 is an impedance matching diagram. The overlapping area of the white line and the black line in the figure is the area of optimal impedance matching. It can be seen that the zinc oxide and ferroferric oxide composite-coated titanium dioxide composite hollow fiber composite absorbing material has strong dielectric loss capability and good impedance matching characteristics.
[0085] from Figure 6It can be seen that the composite hollow fiber absorber material of zinc oxide and ferroferric oxide coated with titanium dioxide has excellent electromagnetic wave absorption performance. When the thickness is 4.96mm, the absorption effect of electromagnetic waves is the best, and the effect of -57.84dB is obtained.
[0086] Comparative Example 1
[0087] The difference from Example 1 is that the reaction in step (4) is not carried out, and the rest remains unchanged to obtain zinc oxide composite ferroferric oxide hollow fiber. Electromagnetic parameter testing is performed using an Agilent Technologies E8363A electromagnetic wave vector network analyzer, and the wave absorption performance of the material is calculated based on the electromagnetic parameters, and the wave absorption effect is poor.
[0088] Figure 7 This is a SEM image of the material prepared in Comparative Example 1. It can be seen that the zinc oxide composite ferroferric oxide hollow fibers prepared by this method have uniform size, and the fiber surface is relatively rough, and the large particles on the surface are zinc oxide particles; Figure 8 The performance diagram of the sample prepared in the comparative example shows that in the range of 2-18 GHz, the reflection loss is far less than that in Example 1, and the wave absorbing performance is poor.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a zinc-iron composite oxide-coated titanium dioxide hollow fiber, characterized in that: The steps include: The zinc salt and the iron salt are uniformly dispersed in a solvent by using a surfactant, and then electrospinning is performed to obtain zinc-iron based fibers; The zinc salt is zinc nitrate hexahydrate, zinc chloride or zinc acetate dihydrate; The iron salt is ferric acetylacetonate, ferric nitrate nonahydrate or ferric acetate tetrahydrate; The surfactant is polyvinyl pyrrolidone or polyacrylonitrile; The solvent is N,N-dimethylformamide; The mass of zinc salt, iron salt and surfactant added to each milliliter of solvent is 0.01-0.4g, 0.01-0.4g and 0.01-0.8g; The voltage of the electrospinning is 8-15 kV, and the feed rate is 0.1-0.8 mL / h; The zinc-iron-based fiber is heated and calcined in air, and then reduced in hydrogen to obtain a precursor; The zinc-iron-based fiber is heated and calcined in air at a temperature of 300-600°C, a heating rate of 1-5°C / min, and a reaction time of 0.5-5h; The method of reducing the precursor in hydrogen is as follows: calcining at 450-550° C. for 1.5-2.5 h in a hydrogen atmosphere to obtain the precursor; The precursor is mixed with a titanium source and ethanol to undergo a solvothermal reaction to obtain a product; The titanium source is tetrabutyl titanate, tetraethyl titanate or tetraisopropyl titanate; The mass ratio of the precursor to the titanium source is 0.05-1:0.05-1; The temperature of the solvothermal reaction of the precursor and the titanium source is 100-200° C., and the reaction time is 6-15 hours; Among them, zinc exists in the form of zinc oxide, and iron exists in the form of ferroferric oxide.
2. The method for preparing the zinc-iron composite oxide-coated titanium dioxide hollow fiber according to claim 1, characterized in that: The masses of zinc salt, iron salt and surfactant added to each milliliter of solvent are 0.01-0.2g, 0.01-0.2g and 0.1-0.3g.
3. The method for preparing the zinc-iron composite oxide-coated titanium dioxide hollow fiber according to claim 1, characterized in that: The voltage of electrospinning was 10-13 kV and the feed rate was 0.1-0.5 mL / h.
4. The method for preparing the zinc-iron composite oxide-coated titanium dioxide hollow fiber according to claim 1, characterized in that: The electrospinning voltage was 11 kV and the feed rate was 0.3 mL / h.
5. The method for preparing the zinc-iron composite oxide-coated titanium dioxide hollow fiber according to claim 1, characterized in that: The heating calcination temperature is 400-550°C, the heating rate is 1-3°C / min, and the reaction time is 1-3h.
6. The method for preparing the zinc-iron composite oxide-coated titanium dioxide hollow fiber according to claim 1, characterized in that: The method of reducing the precursor in hydrogen is as follows: in a hydrogen atmosphere, the calcination temperature is 500° C. and the calcination time is 2 h.
7. The method for preparing the zinc-iron composite oxide-coated titanium dioxide hollow fiber according to claim 1, characterized in that: The mass ratio of the precursor to the titanium source is 0.05-0.5:0.05-0.
5.
8. The method for preparing the zinc-iron composite oxide-coated titanium dioxide hollow fiber according to claim 1, characterized in that: The temperature for the solvothermal reaction of the precursor and the titanium source is 120-180° C., and the reaction time is 8-13 hours.
9. A zinc-iron composite oxide coated titanium dioxide hollow fiber, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8, wherein zinc exists in the form of zinc oxide, iron exists in the form of ferroferric oxide, the zinc oxide and ferroferric oxide complex exists in the form of hollow fibers, and titanium dioxide is coated on the surface of the hollow fibers.
10. An electromagnetic wave absorbing device, prepared by mixing the zinc-iron composite oxide-coated titanium dioxide hollow fiber according to claim 1 and paraffin.
Citation Information
Patent Citations
ZnO / Co composite nano hollow fiber electromagnetic wave absorption material and preparation method thereof
CN108753251A
Titanium dioxide coated ferroferric oxide hollow microsphere composite material as well as preparation method and application thereof
CN112094622A